2018
DOI: 10.1016/j.ijheatmasstransfer.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Air–liquid interactions in a pressure-swirl spray

Abstract: The energy transfer between a liquid hollow cone spray and the surrounding air has been studied using both imaging and phase-Doppler techniques. The spray was produced by a pressure-swirl atomizer discharging Jet A-1 fuel at inlet over pressures of p = 0.5, 1.0 and 1.5 MPa into quiescent ambient air. The liquid exits the nozzle as a conical film which thins as it spreads and develops long-and shortwave sinusoidal instabilities with breakup occurring, at the length smaller than that predicted by the inviscid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 73 publications
1
12
0
1
Order By: Relevance
“…For spray analysis, Phase Doppler Particle Analyzer (PDPA) technique is the most commonly used diagnostic tool. Jedelsky et al 6 and Guerrassi & Champoussin 7 with the help of PDPA measurements in atmospheric environments, observed that the droplet Sauter mean diameter (SMD) decreases with the increase of radial distance from the central axis. It is noted that for dense spray, PDPA is doubted to be suitable due to the multi-scattering effect.…”
Section: Introductionmentioning
confidence: 99%
“…For spray analysis, Phase Doppler Particle Analyzer (PDPA) technique is the most commonly used diagnostic tool. Jedelsky et al 6 and Guerrassi & Champoussin 7 with the help of PDPA measurements in atmospheric environments, observed that the droplet Sauter mean diameter (SMD) decreases with the increase of radial distance from the central axis. It is noted that for dense spray, PDPA is doubted to be suitable due to the multi-scattering effect.…”
Section: Introductionmentioning
confidence: 99%
“…Marchione et al [8][9][10] studied spray characteristics, such as the spray cone angle and the film breakage length, of the external flow field under different spray pressures. Jedelsky et al [11,12] studied the formation of a hollow cone spray and the chang law of the spray cone angle. Xia et al [13] studied spray characteristics and found that the breaking length of the water jet decreases as the gas-liquid ratio in the air increases.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the spray mean droplets size was reduced by increasing the injection pressure, while a higher effect was pronounced at lower injection pressures. The effect of the pressure on the behavior of droplets was investigated by Liu et al [16], Jedelsky et al [17] and Ge et al [18]. It was concluded that the SMD decreased gradually with the increase in the pressure, and remained constant when the pressure was higher than 20bar.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the SMD decreased gradually with the increase in the pressure, and remained constant when the pressure was higher than 20bar. Jedelsky et al [17] found that the atomizer structure had a great effect on the atomization quality. Several researchers [19][20][21][22][23] had examined the effect of GLR on the mean droplets size distribution and concluded that the latter remained fairly constant as the GLR changed.…”
Section: Introductionmentioning
confidence: 99%